Plant NLR receptor proteins and their potential in the development of durable genetic resistance to biotic stresses. (2019) - Araújo, Amanda Cristina de; Fonseca, Fernando Campos De Assis; Cotta, Michelle Guitton; Alves, Gabriel Sergio Costa; Miller, Robert Neil Gerard
Abstract: In order to meet global food security demands in the next decades, considerable changes are required for sustainable agriculture in the context of plant disease, with sufficient food production depending on the development of durable genetically disease resistant crops. For this, further advances are required in our understanding of the plant innate immune system and how plants respond to invading pathogenic micro-organisms. Over the past 20 years, considerable research has been conducted into the characterization and cloning of plant nucleotide-binding, leucine-rich repeat (NLR) immune receptors. These intracellular receptors can recognize directly or indirectly pathogen effector proteins, resulting in effector-triggered immunity (ETI). Elucidation, however, of the diversity of NLR resistance gene families and the molecular basis of NLR-driven effector recognition and defense signaling is incomplete. Here, we present a summary of the understanding of NLR structure, function, genomic organization and diversity in plants. Recent advances in target enrichment approaches for NLR characterization and function validation are highlighted in the context of NLR engineering possibilities for accelerated durable genetic resistance to biotic stresses.